COVID-19 vaccine uptake and associated factors among pregnant women attending antenatal care in Debre Tabor public health institutions: A cross-sectional study - Chekol Abebe, Endeshaw; Ayalew Tiruneh, Gebrehiwot; Asmare Adela, Getachew; Mengie Ayele, Teklie; Tilahun Muche, Zelalem; Behaile T/Mariam, Awgichew; Tilahun Mulu, Anemut; Abebe Zewde, Edgeit; Dagnaw Baye, Nega; Asmamaw Dejenie, Tadesse (Frontiers in Public Health, 2022)
Background Vaccination is the best means of reducing the increased risk of severe COVID-19 during pregnancy. Data on COVID-19 vaccine uptake among pregnant women in Ethiopia is scarce. Thus, this study aimed to assess COVID-19 vaccine uptake and associated factors among pregnant women. Method An institution-based cross-sectional study was conducted among 634 pregnant women attending antenatal care in Debre Tabor public health institutions from March 14 to 30, 2022. Participants were recruited using a multistage sampling technique and data were collected via face-to-face interviews using a pre-tested structured questionnaire. Stata version 16.0 software was used for data analysis. Multiple logistic regression analysis was used to assess factors associated with COVID-19 vaccine uptake, with a p-value< 0.05 considered statistically significant. Result Only 14.4% (95% CI: 11.7%-17.3%) of participants had received at least one dose of COVID-19 vaccines. The main reasons for declining vaccination were fear that the COVID-19 vaccine may have harmful side effects on the fetus or the mother. Being 45 or older (AOR: 1.75, 95%CI: 1.01–2.95), being married (AOR: 1.26, 95%CI: 1.12, 2.96), having good knowledge (AOR:3.52, 95%CI:1.83–3.87), and a positive attitude (AOR:4.81, 95% CI: 1.42–7.33) were positive predictors of COVID-19 vaccine uptake. But attaining a college or university education (AOR: 0.43, 95%CI: 0.12–0.69) was found to be a barrier to vaccine uptake by pregnant women. Conclusion COVID-19 vaccination among pregnant women was substantially low. Old age, being married, low education, good knowledge, and a positive attitude were significant predictors of COVID-19 vaccine uptake. To enhance the COVID-19 vaccine uptake, the government should improve the knowledge and attitude of pregnant women toward the COVID-19 vaccine.